A fabric-based double rectangular complementary split ring resonator for wideband applications - Zakaria, Zahriladha; Abd. Razak, Intan Shafinaz; Al Gburi, Ahmed Jamal Abdullah; Meor Said, Maizatul Alice; Joret, Ariffuddin; Alam, Syah; Palandoken, Merih (The Electromagnetics Academy, 2025)
This paper introduces a novel wideband antenna composed of fabric materials suitable for wearable and flexible applications and a straightforward single-unit Metamaterial (MTM). The antenna design employs ShieldIT Super as the conductive fabric and felt as the dielectric substrate, creating a lightweight and adaptable solution with dimensions of 58 mm × 34 mm × 2 mm. Operating over a frequency range of 1.88 to 6.88 GHz, the proposed antenna achieves a peak gain of 4.72 dBi and a radiation efficiency of 94%. The antenna has a wide measured bandwidth from 1.2 to 3.5 GHz (97%) and 4.0 to 5.9 GHz (38%), with an average measured gain of 3 dBi in the lower band and 4.6 dBi in the upper band. The MTM-inspired design features a double rectangular complementary split-ring resonator at the center of the radiating patch, which enhances bandwidth. The MTM structure exhibits Epsilon-Near-Zero (ENZ) and Mu-Negative (MNG) properties. This novel design illustrates significant advancements in wideband antenna performance and is suitable for wearable fabric-based S band, C band, 5G, Wireless Body Area Network (WBAN), and microwave imaging applications.